2018
DOI: 10.1111/adb.12608
|View full text |Cite
|
Sign up to set email alerts
|

Drinking despite adversity: behavioral evidence for a head down and push strategy of conflict‐resistant alcohol drinking in rats

Abstract: Compulsive alcohol drinking, where intake persists regardless of adverse consequences, plays a major role in the substantial costs of alcohol use disorder. However, the processes that promote aversion-resistant drinking remain poorly understood. Compulsion-like responding has been considered automatic and reflexive and also to involve higher motivation, since drinking persists despite adversity. Thus, we used lickometry, where microstructural behavioral changes can reflect altered motivation, to test whether c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(100 citation statements)
references
References 46 publications
20
80
0
Order By: Relevance
“…To understand whether EtOH dependence altered patterns of consummatory behavior to contribute to the increase in EtOH consumption, we examined licking microstructure across training (Bin et al, ; Darevsky et al, ; Davis, ; Griffin et al, ; Robinson and McCool, ) (Fig. A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand whether EtOH dependence altered patterns of consummatory behavior to contribute to the increase in EtOH consumption, we examined licking microstructure across training (Bin et al, ; Darevsky et al, ; Davis, ; Griffin et al, ; Robinson and McCool, ) (Fig. A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, minimal research has investigated sex differences in EtOH seeking that occurs despite adverse consequences. Research investigating compulsive‐like EtOH seeking includes a number of models, involving punished operant self‐administration and consumption of quinine‐adulterated EtOH (Darevsky et al., ; Hopf and Lesscher, ; Radke et al., ). Recent research has identified similar sensitivities to quinine adulteration in males and females, suggesting that sex differences are not present in this form of inflexible EtOH taking (Sneddon et al., ).…”
mentioning
confidence: 99%
“…Preclinical animal models of excessive EtOH consumption typically display "front-loading" behavior, wherein the amount or proportion of EtOH consumed is highly skewed toward the onset of EtOH access. This phenomenon is often observed following many drinking experiences and has therefore been suggested to reflect a progressive increase in the motivation to experience EtOH's subjective rewarding effects (Darevsky et al, 2018;Linsenbardt and Boehm, 2014;Linsenbardt and Boehm, 2015;Rhodes et al, 2007;Salling et al, 2018;Wilcox et al, 2014).…”
mentioning
confidence: 99%